solve x + y = 7, 3x – y = 1 by method of substituion​

Question

solve x + y = 7, 3x – y = 1 by method of substituion​

in progress 0
Margaret 4 weeks 2021-08-18T18:10:33+00:00 2 Answers 0 views 0

Answers ( )

  1. Charlotte
    0
    2021-08-18T18:11:38+00:00

    y=27/2

    Step-by-step explanation:

    3y-27-y=1y=27/2

    equation same on x+y=7

  2. Charlotte
    0
    2021-08-18T18:12:12+00:00

    Answer:

    \huge\bold\star\blue{Answer}\star

    x + y = 7

    => y = 7 – x —-( 1 )

    3x – y = 1 —-( 2 )

    Substitute y = 7 – x in equation ( 2 ),

    we get

    3x – ( 7 – x ) = 1

    => 3x – 7 + x = 1

    => 4x = 8

    => x = 8/2

    => x = 4

    Put x = 4 in equation ( 1 ), we get

    y = 7 – 4

    => y = 3

    Therefore ,

    ( x , y ) = ( 4 , 3 )

Leave an answer

Browse
Browse

18:9+8+9*3-7:3-1*13 = ? ( )